(Plenary) The Revival of Compound Semiconductors and How They Will Change the World in a 5G/6G Era. (8th September 2020) - Collaert, Nadine; Alian, AliReza; Banerjee, Aritra; Chauhan, Vikas; ElKashlan, Rana Y.; Hsu, Brent; Ingels, Mark; Khaled, Ahmad; Kodandarama, Komal Vondkar; Kunert, Bernardette; Mols, Yves; Peralagu, Uthayasankaran; et al.
Abstract : The world is more than ever relying on connectivity in our daily life as well as our professional life. With 5G being rolled out, the industry is looking already at the next generation of mobile communication to bring even higher speeds and more connections than previous generations. But with 5G we are at an inflection point where it is not only about higher data rates and more connections, but about connecting different kind of devices and the new ways humans and machines interact with each other. The higher frequencies, low latency and reliability requirements will put a lot of strain on the technologies to enable this. While CMOS is the preferred vehicle, to fulfill these demands compound semiconductors like GaN and InP might be the better options for particular functions of the radio architecture. This paper will address the progress toward upscaling these materials to a Si platform and to make them CMOS and 3D compatible to enable the final heterogeneous systems that will be needed for 5G and beyond.